Adolescent and Adult Time Inventory-Time Attitude Scales: validity and contributions to physical activity and self-concept in Spanish adolescents - Konowalczyk, Svenja; Mello, Zena R.; Röske, Lisa A. S.; Buhl, Monika; Heim, Rüdiger; Worrell, Frank C. (International perspectives in psychology, 2020)
In this study, we examined the psychometric properties for the time attitude subscales of the Adolescent and Adult Time Inventory-Time Attitude Scale–Spanish (AATI-TA–Spanish). We sought to determine the internal consistency, structural validity, gender and age invariance, and convergent validity of scores on the six subscales: Past Positive, Past Negative, Present Positive, Present Negative, Future Positive, and Future Negative. Participants were 789 Spanish adolescents. Reliability estimates indicated high internal consistency across the subscales. Conﬁrmatory factor analyses provided strong support for the theorized 6-factor structure. Conﬁgural, metric, and scalar invariance was demonstrated for gender and early and late adolescent groups. Convergent validity was shown for physical activity and self-concept. Overall, results provided strong psychometric evidence that Adolescent and Adult Time Inventory-Time Attitude Scale–Spanish scores may be used effectively with Spanish adolescents.